Electrophoretic Distribution of the Proteins and Glycoproteins of Influenza Virus and Sendai Virus - Content, Jean (1970)
The proteins of influenza (WSN) and Sendai virus have been separated by polyacrylamide gel electrophoresis into five components. In both cases, three of these components were shown to be glycoproteins containing fucose, galactose, and glucosamine. Two protein components of each virus were probably free from these sugar residues, including the structural unit of the viral ribonucleoprotein (molecular weight of about 60,000 daltons).